2006
DOI: 10.1002/ajmg.a.31286
|View full text |Cite
|
Sign up to set email alerts
|

Autistic behavior in children with fragile X syndrome: Prevalence, stability, and the impact of FMRP

Abstract: We examined autistic behavior in a cross-sectional sample of 179 children with fragile X syndrome (FXS) and a longitudinal subset of 116 children using the Childhood Autism Rating Scale (CARS) to (a) determine a prevalence of autistic behavior in FXS, (b) examine the stability of autistic ratings over time, and (c) assess the association between the fragile X mental retardation protein (FMRP) and autistic behavior. Approximately 21% of the sample of 129 children (25.9% of boys) scored at or above the cutoff fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
284
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(302 citation statements)
references
References 44 publications
13
284
2
3
Order By: Relevance
“…Approximately 20% of boys with fragile X syndrome meet diagnostic criteria for ASDs when evaluated by objective criteria. 11,47 Two early studies found an incidence of abnormal fragile X studies of 6% in unselected cohorts of boys with ASDs. These studies noted 4 of 75 (5.3%) 48 and 17 of 210 (8%) 49 positive rates.…”
Section: Single-gene Disordersmentioning
confidence: 99%
“…Approximately 20% of boys with fragile X syndrome meet diagnostic criteria for ASDs when evaluated by objective criteria. 11,47 Two early studies found an incidence of abnormal fragile X studies of 6% in unselected cohorts of boys with ASDs. These studies noted 4 of 75 (5.3%) 48 and 17 of 210 (8%) 49 positive rates.…”
Section: Single-gene Disordersmentioning
confidence: 99%
“…FXS is a frequent monogenic cause of ASD 74,[76][77][78] and the behavioral overlap between autism and FXS patients suggests overlapping neuronal network mechanisms that increase susceptibility to ASD. The regulatory function of CYFIP1 in the context of FMRP-and WAVE-containing complexes and subsequent actin remodeling may explain the convergence of these two neurodevelopmental disorders.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[1][2][3][4][5] FXS is caused by a full mutation, an expansion of CGG trinucleotide repeats (4200 CGG repeats) in the 5'UTR of the FMR1 gene. Individuals harboring an allele with 55-200 CGG repeats are premutation carriers.…”
Section: Introductionmentioning
confidence: 99%